Criminal Law Protection For Local Wisdom And Traditional Knowledge In Indonesia - Resianna Lamria Nadeak; Eko Riyadi; Cik Marhayani (IHSA Institute, 2026)
Criminal law protection for local wisdom and traditional knowledge in Indonesia is essential for safeguarding and preserving the nation’s cultural heritage. This study aims to evaluate the effectiveness of existing criminal law regulations in protecting local wisdom and traditional knowledge from misuse and exploitation. Using a qualitative research method with a Systematic Literature Review (SLR) approach, this study analyzes various relevant literature and regulations to identify and evaluate the success of the law in providing protection. Additionally, this study identifies the challenges and obstacles faced in the implementation of criminal law protection, including social, cultural, and institutional factors. The results indicate that while existing regulations have provided a legal foundation, various challenges still hinder the achievement of optimal protection. These findings are expected to provide recommendations for policymakers in their efforts to enhance legal protection for local wisdom and traditional knowledge in Indonesia